2019
DOI: 10.1002/anie.201901242
|View full text |Cite
|
Sign up to set email alerts
|

Regio‐ and Enantio‐selective Chemo‐enzymatic C−H‐Lactonization of Decanoic Acid to (S)‐δ‐Decalactone

Abstract: The conversion of saturated fatty acids to high value chiral hydroxy-acids and lactones poses anumber of synthetic challenges:t he activation of unreactive CÀHb onds and the need for regio-and stereoselectivity.H ere the first example of aw ild-type cytochrome P450 monooxygenase (CYP116B46 from Tepidiphilus thermophilus) capable of enantio-and regioselective C5 hydroxylation of decanoic acid 1 to (S)-5hydroxydecanoic acid 2 is reported. Subsequent lactonization yields (S)-d-decalactone 3,ahigh value fragrance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
60
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 37 publications
(64 reference statements)
0
60
0
Order By: Relevance
“…The GC‐FID analysis of the extracted norcamphor lactone showed that the enzyme was able to convert 100% of the substrate norcamphor in 24 h at this reaction scale (Figure S1). Biocatalytic routes to the other lactone comonomer (ε‐CL) in this study ( vide infra ) and δ‐DL have recently been reported …”
Section: Resultsmentioning
confidence: 68%
“…The GC‐FID analysis of the extracted norcamphor lactone showed that the enzyme was able to convert 100% of the substrate norcamphor in 24 h at this reaction scale (Figure S1). Biocatalytic routes to the other lactone comonomer (ε‐CL) in this study ( vide infra ) and δ‐DL have recently been reported …”
Section: Resultsmentioning
confidence: 68%
“…[24] Additionally, CYP505E3 could be employed for the synthesis of valuable diols and lactones. Alternative biocatalytic processes for the synthesis of C10 and C12 d-lactones are highly sought after [4,22] given that expensive natural substrates, variable supply, and environmental concerns [25] present challenges to processes currently used for the industrial production of "natural" lactones from unsaturated massoia d-lactones. [26]…”
Section: Zuschriftenmentioning
confidence: 99%
“…[1][2][3] However, there are several P450s that show in-chain hydroxylation of medium-chain fatty acids such as decanoic acid and dodecanoic acid, although hydroxylation is rarely more in-chain than the w-6 position. [3] One exception in this regard is CYP116B46 from Tepidiphilus thermophiles [4] which gives C5 hydroxylation of decanoic and dodecanoic acid. In the case of decanoic acid, it displays exquisite regioselectivity (99 %) and enantioselectivity to produce the "non-natural" (S)-d-decalactone with greater than 90 % ee.…”
mentioning
confidence: 99%
“…Enzymes are potent biocatalysts that are able to carry out numerous chemical transformations with remarkable chemo‐, regio‐ and stereo‐selectivity . The intrinsic sustainability of enzymatic processes along with the use of green reaction conditions such as absence of potentially toxic solvents, and activation with non‐conventional sources of energy has expanded the use of biocatalysis in both chemical industries and in academic institutions, focusing in drug discovery and in the synthesis of molecules with relevant biological activity .…”
Section: Introductionmentioning
confidence: 99%
“…Enzymes are potent biocatalysts that are able to carry out numerous chemical transformations with remarkable chemo-, regio-and stereo-selectivity. [1][2][3][4][5] The intrinsic sustainability of enzymatic processes along with the use of green reaction conditions such as absence of potentially toxic solvents, and activation with non-conventional sources of energy has expanded the use of biocatalysis in both chemical industries and in academic institutions, focusing in drug discovery and in the synthesis of molecules with relevant biological activity. [6][7][8] Recent developments in protein engineering and enzyme directed evolution, [9,10] together with the availability of efficient methods for the production of recombinant molecules, have led to rapidly expanding new fields in biocatalysis.…”
Section: Introductionmentioning
confidence: 99%